2005
DOI: 10.1161/01.hyp.0000150783.79172.bb
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Uric Acid Predicts Adult Blood Pressure

Abstract: Abstract-Uric acid has been proposed as an important risk factor in the development of primary hypertension in humans.However, limited information is available linking childhood uric acid levels and blood pressure levels in adulthood. This study examined 334 whites and 243 blacks enrolled in the Bogalusa Heart Study as children aged 5 to 17 years and as adults aged 18 to 35 years. The average follow-up period was 12 years. Childhood uric acid was significantly correlated with childhood and adult blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
210
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(228 citation statements)
references
References 21 publications
9
210
0
9
Order By: Relevance
“…Regarding the mean age of the individuals in this series (50.3 years), there are no significant differences in relation to most studies on the subject 3,18 , except for the studies carried out in children and adolescents, such as the one by Bogalusa 14 or the trial carried out by Forman et al 26 , in which mean age was 61 years.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Regarding the mean age of the individuals in this series (50.3 years), there are no significant differences in relation to most studies on the subject 3,18 , except for the studies carried out in children and adolescents, such as the one by Bogalusa 14 or the trial carried out by Forman et al 26 , in which mean age was 61 years.…”
Section: Discussionmentioning
confidence: 55%
“…Several studies have demonstrated that UA is an independent risk variable for cardiovascular risk factors [2][3][4][5][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials suggest that uric acid has a role in the development of hypertension, at least in adolescents and adolescents with obesity. 11,12 This is supported by epidemiological data, 20 including studies in adult populations. [1][2][3] Our study included only adults with a known diagnosis of hypertension attending a specialist hypertension service.…”
Section: Discussionmentioning
confidence: 73%
“…Masuo et al evaluate the linear association of serum uric acid and systolic blood pressure, finding an average increase of 23mm Hg per 1mg/dl increase in serum uric acid among nonobese young men [9]. In an ethnically diverse population within the Bogalusa Heart Study, higher childhood and young adult serum uric acid levels associated with incident hypertension progressive increase in blood pressure within the normal range [10]. A recent re-evaluation of the Framingham Heart Study data also suggests that higher serum uric acid levels is associated with increased risk of progression from normal blood pressure (bp) to hypertension [11].…”
mentioning
confidence: 99%